Effects of industrial diversity on economic stability: A panel GARCH process to predict economic stability - Sajid Noor; Christopher A. Erickson (Review of Economic Analysis (REA), 2023)
This paper studies the relationship between industry diversity and economic stability. The economic stability has been estimated using a panel-GARCH model. Our sample consists of US county-level data for the period 2003 to 2017. The results suggest that industry diversity improves economic stability and reduces a region's unemployment rate. However, this study finds a negative relationship between industry diversity and economic growth. Although diversity negatively affects economic growth, it minimizes income loss when the nation falls into an economic recession. Therefore, we cannot conclude a tradeoff between economic stability and economic growth. It is possible that a region can achieve both stability and growth together through industry diversification. This paper also explores that the effects of diversity on economic stability, unemployment rate, and economic growth may vary between different counties depending on their metro or non-metro status. Thus, this paper suggests that policymakers may choose industry diversification as a strategy to achieve long-run economic stability and precaution against an unexpected economic downturn.
Keywords: O; 330; Diversity; Stability; Panel GARCH; Income Volatility; Recession; Economic Growth; Industry; Herfindahl; Hachman